Pengaruh Store Atmosphere dan Keragaman Menu Terhadap Keputusan Pembelian pada Samara Coffee Pekanbaru - Rahmah Mei Lindra; Endang Sutrisna (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
In recent years, the cafe industry in Indonesia has experienced very rapid development. The increasingly dynamic lifestyle of society and the increasing interest in coffee have triggered the growth of coffee shops in various cities. This study aims to determine the effect of store atmosphere and menu diversity on purchasing decisions at Samara Coffee, Pekanbaru. This study uses a quantitative method. The sampling technique is non-probability sampling including incidental/accidental sampling with a sample size of 100 respondents. The data obtained were processed using SPSS software version 25. The results of this study are: (1) store atmosphere has a significant effect on purchasing decisions, (2) menu diversity has a significant effect on purchasing decisions, (3) store atmosphere and menu diversity have a significant effect on purchasing decisions.